Exploring The Figurative Language Landscape In “Moana” Movie (A Semantics Analysis on Figurative Language) - Tinambunan, Toibah Hasanah; Sihite, Meida Rabia; Prihatini, Syafrina (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The goals of the research were to identify the many forms of symbolic language employed in the film